Investigation of Paramedics, Attitude, Knowledge and Practice regarding the Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in Iran - Giti Kashi; Nafiseh Nourieh (Shiraz University of Medical Sciences, 2023)
Background: The Middle East Respiratory Syndrome coronavirus (MERS-Co V) was known as a human pathogen associated with respiratory symptoms. This study aimed to investigate attitudes, knowledge, and practice about MERS-CoV in paramedics.Methods: In this quasi-experimental study, 82 paramedics in Iran in April 2019 were selected in a stratified cluster sampling. Paramedics worked in Health Centers in Iran. We performed educational intervention in this study. A four-point Likert scale researcher-made questionnaire containing demographic (9 questions) and MERS-CoV (33 questions) items was administered to collect the data. The collected data were analyzed by SPSS 18 software.Results: Out of 82 paramedics, who completed questionnaires, 42.7% (35 people) were male, 56.1% (46 people) had a diploma degree, and 19.5% (16 people) had less than 1 year of work experience. about the participants reported 2 laboratoryconfirmed infections at Kerman State. In addition, 67.1% (32 people) passed a course to become familiar with disease. Theparamedics' mean age was 37.52±8.88. The knowledge mean score of paramedics was 12.82 (SD=10.04). The highly significant source of data collection in paramedics was the attendance in a course to become familiar with disease (43.9%, 36). The mean score of the practice of paramedics was 13.98 (SD=10.00). The most significant concern in neglecting travel to polluted areas in paramedics was public health defects (39%, 32). There was a significant relationship (P<0.05, t=9.06) between knowledge score and variables: gender (P=0.001), education level (P=0.001), and years in service (P=0.039).Conclusion: The paramedic had concerns and tend to increase the knowledge regarding prevention. The awareness of the transmission of diseases was the most important factor for modifying practice and preventing diseases. Health decisionmakers recognized preventive actions to hinder the transmission of this fatal virus.